2015
DOI: 10.1212/wnl.0000000000002023
|View full text |Cite
|
Sign up to set email alerts
|

Seizures as adverse events of antibiotic drugs

Abstract: Evidence for an association between antibiotic drugs and symptomatic seizures is low to very low (evidence Class III-IV). Despite this, numerous reports point to an increased risk for symptomatic seizures especially of unsubstituted penicillins, fourth-generation cephalosporins, imipenem, and ciprofloxacin in combination with renal dysfunction, brain lesions, and epilepsy. During administration of such antibiotics in patients with particular predispositions, close monitoring of serum levels is advocated. As mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 59 publications
2
134
1
14
Order By: Relevance
“…Risk of minor adverse events such as mild headache, tinnitus, cutaneous discomfort, neck muscle contraction, nausea, light headedness or syncope, unilateral eye pain and lacrimation remains <5%. To put this into perspective, the risk of seizures with penicillins and carbapenem drugs is up to 5%63 and increases further with predisposing factors. To date, meta-analyses of published treatment trials of TMS64–66 have been reassuring and support safe use of TMS in patients and healthy volunteers.…”
Section: Safety Considerationsmentioning
confidence: 99%
“…Risk of minor adverse events such as mild headache, tinnitus, cutaneous discomfort, neck muscle contraction, nausea, light headedness or syncope, unilateral eye pain and lacrimation remains <5%. To put this into perspective, the risk of seizures with penicillins and carbapenem drugs is up to 5%63 and increases further with predisposing factors. To date, meta-analyses of published treatment trials of TMS64–66 have been reassuring and support safe use of TMS in patients and healthy volunteers.…”
Section: Safety Considerationsmentioning
confidence: 99%
“…5 As such, most reports of seizures associated with these agents emerge from their use in high doses (often in the treatment of CNS infections) or in renal failure. 6 Carbapenems more readily penetrate the CNS and their use is associated with an increased seizure risk compared with non-carbapenem antibiotics. 7 Among the carbapenems, imipenem is generally thought to have the highest risk.…”
Section: Beta-lactamsmentioning
confidence: 99%
“…13 Seizures are rare but have been reported, particularly with ciprofloxacin in the context of other susceptibility factors. 6 Macrolides, tetracyclines, aminoglycosides and glycopeptides have not been associated with seizures. 6 …”
Section: Other Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported neurotoxicity of imipenem, especially in patients with brain injury [3, 4]. More recently, several authors have reported neurotoxicity with cefepime.…”
mentioning
confidence: 99%